The Construction of Masculinity Myths in the Namin Group's Bajidoran Arena as a Specific Gender Order - Saepudin, Asep; Djohan, Djohan; Sunardi, Stanislaus (Institut Seni Indonesia Yogyakarta, 2023)
The Sundanese people have long recognized bajidoran as an entertainment art form that presents the aesthetics of dance and traditional Sundanese music (karawitan). However, beneath this surface lies the complexity of power struggles and masculine domination among individuals involved in the Bajidoran Enthusiast Community (Komunitas Pecinta Bajidoran or KPB). Interestingly, the power struggles are not limited to men but also involve women. This phenomenon prompts an inquiry into why bajidoran is heavily associated with practices of masculinity. This study aims to address the following questions: why is bajidoran associated with practices of masculinity, how is this construction process carried out, what are the contributing factors, and what are the implications for the KPB?This research employs a qualitative method with an ethnographic approach, wherein the researcher values the experiences and realities of the subjects under study, even if they differ radically from their own. The researcher applies three characteristics of this new ethnography: honesty, towards other facts, self-reflection, and polyvocality. Data collection involves literature review, observation, interviews, and documentation.The findings of the research explain that: 1) masculinity is strongly embedded in bajidoran due to: firstly, cultural, daily practices, and historical contexts that construct masculinity, which are dialectically intertwined with the experiences of the KPB, both present and past. Secondly, the situational and practical conditions within the bajidoran arena (social relations and interactions) have great potential to generate masculinity. 2) The process of constructing masculinity involves seven stages: production, socialization, appreciation, internalization and externalization, relationships and interactions, staging, and formation. Eight factors contribute to the construction of masculinity: patterns/sequences, the role of the mc and pesinden (vocalists), pencug ibing (leader), kendang (drum), selendang (scarf), economic capital, alcoholic beverages, and musical elements. The results of this research provide insights for the Bajidoran Enthusiast Community and relevant institutions to reconstruct the staging of masculinity in a way that accommodates gender equality.